2014
DOI: 10.1007/s10620-014-3386-x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Retrograde Cholangiography Using an Anterior Oblique-Viewing Endoscope in Patients with Altered Gastrointestinal Anatomy

Abstract: Background Endoscopic retrograde cholangiopancreatography (ERCP) is technically more challenging in patients who have undergone gastrointestinal (GI) reconstruction.AimsThe aim of this study was to evaluate the utility of the anterior oblique-viewing endoscope (AOE) for ERCP in patients with a retained major duodenal papilla after GI reconstruction.MethodsThis was a retrospective study involving 40 patients (50 procedures) with a retained papilla after GI reconstruction who underwent ERCP using AOE. Reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Because the median patency time of plastic stents is 3 months or less, metal stents are generally placed in patients with unresectable disease who are expected to survive for longer than 3 months [9]. In patients with a gastrointestinal reconstruction, uncovered self-expandable metal stent (SEMSs) have been placed with the use of a commercially available balloon enteroscope or an anterior obliqueviewing endoscope [1,2,10]. However, the channel diameter of these endoscopes is only 2.8 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Because the median patency time of plastic stents is 3 months or less, metal stents are generally placed in patients with unresectable disease who are expected to survive for longer than 3 months [9]. In patients with a gastrointestinal reconstruction, uncovered self-expandable metal stent (SEMSs) have been placed with the use of a commercially available balloon enteroscope or an anterior obliqueviewing endoscope [1,2,10]. However, the channel diameter of these endoscopes is only 2.8 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic success rate in patients who had undergone Billroth II gastrectomy ranged from 76.2% to 91.7% with a side-viewing endoscope and from 62.5% to 91.3% with a forward-viewing endoscope (Table 5). 3,4,6,[9][10][11][12][13][14] In addition to the differences in endoscopic techniques, endoscopist experience, study design, use of endoscopic sphincterotomy and endoscopic papillary balloon dilatation, indications for ERCP, and differences in the number of patients included in the studies contributed to the wide range of success rates. In this study, the therapeutic success rate was 64%, which was quite low compared with that reported in the literature, but our technical success rate (81.3%) was consistent with that reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…These features render this oblique-viewing endoscopes as perfect tool for performing ERCP in patients with Billroth II reconstruction anatomy. Some Japanese studies have demonstrated a high success rate of ERCP in patients with prior BII reconstruction by using an oblique viewing endoscope (Kikuyama, Sasada, Matsuhashi, Ota, & Nakahodo, 2009;Nakahara, Okuse, Suetani, Morita, Michikawa, Ozawa, Hosoya, Nomoto, Kobayashi, Otsubo, & Itoh, 2015).…”
Section: Choice Of the Scopementioning
confidence: 99%